1985
DOI: 10.1139/v85-200
|View full text |Cite
|
Sign up to set email alerts
|

The electronic absorption spectra of some coumarins. A molecular orbital treatment

Abstract: The electronic absorption spectra of coumarin and its derivatives umbelliferone (6-hydroxycoumarin), esculetin (6,7-dihydroxycoumarin), and scopoletin (6-methoxy-7-hydroxycoumarin) were investigated. The n → π* transition was not observed in the spectrum of coumarin but was observed in the spectra of some of its derivatives. Molecular orbital calculations, using the INDO procedures, were carried out on coumarin and some of its derivatives. The activities of the different sites of the molecules are discussed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 15 publications
2
46
1
Order By: Relevance
“…From this figure, it was found that the polymer P3 a exhibited two absorption maxima at 280 nm and 311 nm, which were assigned to p-p* transitions of coumarin ring. [35,36] The spectrum of P3 g was similar to that of P3 a, which meant that the ethyloxycarbonylmethyl group had no influence on the absorption spectrum of the coumarin ring because the substituent had no resonance effect with the coumarin unit. On the contrary, when the ethyloxycarbonyl group was introduced into the coumarin ring (P3 d and P3 f), a clear redshift was observed in the long wave absorption range.…”
Section: Uv-vis Absorption Spectramentioning
confidence: 92%
“…From this figure, it was found that the polymer P3 a exhibited two absorption maxima at 280 nm and 311 nm, which were assigned to p-p* transitions of coumarin ring. [35,36] The spectrum of P3 g was similar to that of P3 a, which meant that the ethyloxycarbonylmethyl group had no influence on the absorption spectrum of the coumarin ring because the substituent had no resonance effect with the coumarin unit. On the contrary, when the ethyloxycarbonyl group was introduced into the coumarin ring (P3 d and P3 f), a clear redshift was observed in the long wave absorption range.…”
Section: Uv-vis Absorption Spectramentioning
confidence: 92%
“…9 The spectrum of coumarin contains a single transition centered at 320 nm that arises from a strongly allowed π-π* transition overlapping with a weaker 𝑛-π* transition. 10 The absorption spectra of the PQCP complex are essentially the sum of the PQand coumarin spectra, indicating there are no intramolecular interactions between the ring systems of the two chro- mophores within the complexes.…”
mentioning
confidence: 99%
“…The absorption spectra of F221 and F222 are very similar to that of the basic chromophore esculetin [3] and remain essentially unchanged upon binding of Na § or K § All fluorescence emission spectra are characterized by a broad band at k=u 470 nm (excitation at 360 nm). Binding of Na § to F221 and of K § to F222 leads to large fuorescence intensity changes (Fig.…”
Section: Spectroscopic Properties Of F221 and F222mentioning
confidence: 86%